Co-digestion of sewage sludge and food waste in a wastewater treatment plant based on mainstream anaerobic membrane bioreactor technology: A techno-economic evaluation. (June 2021) - Vinardell, Sergi; Astals, Sergi; Koch, Konrad; Mata-Alvarez, Joan; Dosta, Joan
Highlights: The economic feasibility to co-digest sewage sludge and food waste was evaluated. The higher electricity revenue offsets the higher cost in co-digestion scenarios. Treating nutrient backloads in the sidestream was costlier than in the mainstream. Biosolids disposal cost was the most important gross cost contributor. Food waste gate fee had a noticeable impact on co-digestion economic feasibility. Abstract: The implementation of anaerobic membrane bioreactor as mainstream technology would reduce the load of sidestream anaerobic digesters. This research evaluated the techno-economic implications of co-digesting sewage sludge and food waste in such wastewater treatment plants to optimise the usage of the sludge line infrastructure. Three organic loading rates (1.0, 1.5 and 2.0 kg VS m −3 d −1 ) and different strategies to manage the additional nutrients backload were considered. Results showed that the higher electricity revenue from co-digesting food waste offsets the additional costs of food waste acceptance infrastructure and biosolids disposal. However, the higher electricity revenue did not offset the additional costs when the nutrients backload was treated in the sidestream (partial-nitritation/anammox and struvite precipitation). Biosolids disposal was identified as the most important gross cost contributor in all the scenarios. Finally, a sensitivity analysis showed that food waste gate fee had a noticeable influence on co-digestion economic feasibility.